“A Past Which Has Never Been a Present”. Cinema and Photography in Blow-Up by Michelangelo Antonioni - Eugeni, Ruggero (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2008)
This article analyses Michelangelo Antonioni’s Blow-Up (1966). The author argues that the film offers a fully-developed theory of photography, one that is consistent with Merleau-Ponty’s phenomenology and which emphasizes the embodiedness and situatedness of ‘Operator’ and ‘Spectator’. However, one key element of this theory resides in the recognition that these two ‘agents’ can never coincide.